A rare case of transplant hepatectomy for metachronous colorectal cancer metastasis (de novo) - V. E. Zagainov; N. M. Kiselev; D. V. Komarov; S. A. Vasenin; E. A. Ashimov; D. S. Myalik; S. V. Gamayunov; S. V. Romanov; E. N. Ryabova (Вестник трансплантологии и искусственных органов)
In the presented case, a patient who underwent liver transplant procedure for cirrhosis resulting from chronic hepatitis C was diagnosed with colorectal cancer 12 years after the operation. A combined treatment plan consisting of right hemicolectomy followed by nine cycles of adjuvant polychemotherapy using the FOLFOX6 regimen was performed. Seven months following the conclusion of treatment, 22×35 mm foci in segment 8 was detected as a sign of metastatic liver disease. The patient had a transplant hepatectomy. At present, the relapse-free survival is 22 months.